Investigating the Influence of Scs and Pcs on Existence of Human Capital of Rural Entrepreneurial Activities and Small Businesses: Managerial Implications: Array - Agbenyegah, Albert Tchey (Acta Universitatis Danubius. Œconomica, 2020)
Human capital represents one of the primary essentials to successful entrepreneurial activities. As such, there is the need to determine the impact of challenges on the existence of human capital towards rural entrepreneurial activities. This study seeks to empirically investigate the influence of specific and personal challenges on the existence of human capital of entrepreneurial activities. A quantitative approach was adopted aided by a 7 Likert-scale questionnaire to solicit primary data. A total of 300 owner-managers were selected through the snowball and convenience methods. Different analytical tools such as the descriptive statistics, the Exploratory Factor Analysis (EFA), Kaiser-Meyer Olkin (KMO) and the Bartlett Test of Sphericity (BTS) were applied Besides, the Pearson’s correlation coefficient was utilised to test the relationship between the specific challenges (SCs) and personal challenges (PCs) on EHC. Empirically, this study found that SCs and PCs greatly influenced the EHC in terms of entrepreneurial activities. Based on PCs and SCs, it became clear that PCs significantly influenced the EHC in contrast to SCs. The study recommends that more training should be offer to owner-managers through the establishment of local entrepreneurial hubs. Besides, there is the need to provide tailored-made role models to help rural owner-managers of small businesses.